Summarising an Explanation Text with a Visual Representation as the Guidelines: How Does this Work to Represent Meaning? - Mutuota Kigotho; Siti Sarah Fitriani (Institut Agama Islam Negeri Imam Bonjol Padang, 2018)
Metacognition has been popular in reading area, especially when it is related to comprehension and the representation of meanings. Combining metacognitive strategies to represent meanings from a text has been done by previous scholars to help readers construct meaning. In this paper, we present students’ drawings and writings as the results of successive visualisation and summarisation activities in the classroom. We intended to find out the extent to which students’ visual representations can be the guideline for them to write summaries. By employing qualitative research method, we collected visual representations and summaries from 26 undergraduate students studying at the English Education Department of Syiah Kuala University. To understand students’ drawings, we consulted some literature on visual literacy and multimodality; while for the analysis of students’ writings, we reviewed some literature on functional model to language. Based on the analysis, a productive visual representation leads to a strong summary, and vice versa. This result is further discussed in this paper.